Impact of Performance‐Based Financing on effective coverage for curative child health services in Burkina Faso: Evidence from a quasi‐experimental design. Issue 8 (16th May 2021) - Koulidiati, Jean‐Louis; De Allegri, Manuela; Lohmann, Julia; Hillebrecht, Michael; Kiendrebeogo, Joel Arthur; Hamadou, Saidou; Hien, Hervé; Robyn, Paul Jacob; Brenner, Stephan
Abstract: Objective: To evaluate the impact of Performance‐Based Financing (PBF) on effective coverage of child curative health services in primary healthcare facilities in Burkina Faso. Methods: An impact evaluation of a PBF pilot programme, using an experiment nested within a quasi‐experimental design, was carried out in 12 intervention and 12 comparison districts in six regions of Burkina Faso. Across the 24 districts, primary healthcare facilities (537 both at baseline and endline) and households (baseline = 7978 endline = 7898) were surveyed. Within these households, 12 350 and 15 021 under‐five‐year‐olds caretakers were interviewed at baseline and endline respectively. Linking service quality to service utilisation, we used difference‐in‐differences to estimate the impact of PBF on effective coverage of curative child health services. Results: Our study failed to detect any effect of PBF on effective coverage. Looking specifically into quality of care indicators, we detected a positive effect of PBF on structural elements of quality of care related to general service readiness, but not on the overall facility quality score, capturing both service readiness and the content of childcare. Conclusion: The current study makes a unique contribution to PBF literature, as this is the first study assessing PBF impact on effective coverage for curative child health services in low‐income settings. The absence of any significant effects of PBF on effective coverage suggests that PBF programmes require a stronger design focus on quality of care elements especially when implemented in a context of free healthcare policy.